Steam-Based PJBL (Project-Based Learning) Model to Improve Critical Thinking Character of Elementary School - Purnamasari, Rika; Maftuh, Bunyamin; Hakam, Kama Abdul; Hidayat, Mupid; Warlim, Warlim; Ganeswara, Ganjar Muhammad; Ruyadi, Yadi; Dahliyana, Asep; Somad, Momod Abdul (Journal of Educational Sciences, 2026)
The study aims to determine the effectiveness of the STEAM-based Project-Based Learning (PjBL) model in improving critical thinking skills among elementary school students. This research is based on the issue of low critical thinking ability in Science subjects, particularly because the STEAM approach has not yet been applied in learning. The study was conducted at 1 Pawenang Elementary School as an effort to introduce a learning model that integrates Science, Technology, Engineering, Art, and Mathematics. The STEAM-based PjBL syntax includes formulating essential questions, designing project plans, preparing information-gathering schedules, implementing projects, monitoring activities, testing project outcomes, evaluating learning experiences, and drawing conclusions. This study used a mixed-methods approach with a sequential explanatory design. The quantitative phase examined the effectiveness of STEAM in improving students’ critical thinking in Science, while the qualitative phase, through interviews and observations, identified the processes and supporting factors influencing the model’s implementation. The results showed that the STEAM-based PjBL model was effective in enhancing students’ critical thinking skills. Statistical analysis indicated a significance value of 0.001 < 0.05, meaning that the STEAM-based PjBL model had a significant positive effect on the improvement of students’ critical thinking character.